13C-caffeine breath test identifies single nucleotide polymorphisms associated with caffeine metabolism. Issue 3 (June 2020) - Ishii, Michiko; Ishii, Yukimoto; Nakayama, Tomohiro; Takahashi, Yasuo; Asai, Satoshi
Abstract: We performed a caffeine (N-3-methyl- 13 C) breath test (CafeBT) to determine whether it can be employed to identify caffeine metabolism-associated single nucleotide polymorphisms. The study included 130 healthy adults (mean age: 21.9 years). Saliva was collected using an Oragene®DNA saliva collection kit. Breath samples were collected from the subjects. The subjects orally ingested 100 mg 13 C-caffeine dissolved in distilled water. Subsequently, breath samples were collected in bags every 10 min for a total of 90 min. An analysis of 13 CO2 in the expired breath was performed by infrared spectroscopy, and the sum of Δ 13 CO2 over 90 min (S 90m ) was calculated. DNA from saliva samples was genotyped using TaqMan® SNP Genotyping for the following genes: cytochrome P4501A2: rs762551, rs2472297, aryl-hydrocarbon receptor (rs4410790), and adenosine A2A receptor (rs5751876). All subjects had the genotype CC in rs2472297 alleles. No significant difference was observed in S 90m among the genotypes of rs762551 and rs5751876; however, a significant difference was found in S 90m among the genotypes of rs4410790 (C > T). Our findings suggest that the N-3 demethylation of caffeine is dependent on the rs4410790 allele and that CafeBT may be used to determine rs4410790 genotypes. Graphical abstract: Image 1